The Utrecht Work Engagement Scale for Students (UWES–9S): Factorial Validity, Reliability, and Measurement Invariance in a Chilean Sample of Undergraduate University Students - Carmona-Halty, Marcos A.; Schaufeli, Wilmar B.; Salanova, Marisa (Frontiers in Psychology, 2019)
This brief report examines the within–network construct validity of the UWES–9S in a convenience sample of 1502 Chilean students (52% were female) ranging between 18 and 25 years old. The results of confirmatory factor analysis supported a solution with three related factors that fit significantly better than a one-factor solution. The three subscales (i.e., vigor, dedication, and absorption) and the overall UWES–9S showed satisfactory internal consistency. The results of multiple–group confirmatory factor analysis supported gender invariance. Overall, the UWES–9S was found to be a reliable and valid scale to assess academic engagement in Chilean undergraduate university students.